2022
DOI: 10.14814/phy2.15219
|View full text |Cite
|
Sign up to set email alerts
|

Utility of extracellular vesicles as a potential biological indicator of physiological resilience during military operational stress

Abstract: Extracellular vesicles (EVs) transport biological content between cells to mediate physiological processes. The association between EVs and resilience, the ability to cope with stress, is unknown. Using unbiased machine learning approaches, we aimed to identify a biological profile of resilience. Twenty servicemen (27.8 ± 5.9 years) completed the Connor Davidson Resilience (CD‐RISC) questionnaire and were exposed to daily physical and cognitive exertion with 48‐hr sleep and caloric restriction. Blood samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…CD63, CD81, CD9 and Alix were the typical exosomal surface markers and CP05 was a peptide identifieing the CD63 specifically, which had been successifully anchored exosomes to build DDS delivering therapeutic exosomes on the targeting tissues in vivo [ 54 ]. The result of western blot showed PEP1–3 bond with CD63 specifically via their CP05 motifs and PEP3 specifically interacted with CD63 in a stronger affinity than PEP1 and PEP2.…”
Section: Discussionmentioning
confidence: 99%
“…CD63, CD81, CD9 and Alix were the typical exosomal surface markers and CP05 was a peptide identifieing the CD63 specifically, which had been successifully anchored exosomes to build DDS delivering therapeutic exosomes on the targeting tissues in vivo [ 54 ]. The result of western blot showed PEP1–3 bond with CD63 specifically via their CP05 motifs and PEP3 specifically interacted with CD63 in a stronger affinity than PEP1 and PEP2.…”
Section: Discussionmentioning
confidence: 99%
“…All files were normalized using a compensation matrix file generated by the compensation beads. Gating for EVs was performed by defining a side-scatter intensity threshold of 10 5 AU as described previously ( Beckner et al, 2022 ; Conkright et al, 2022 ). EVs with a positive fluorescence intensity following spectral compensation were considered to express the marker.…”
Section: Methodsmentioning
confidence: 99%
“…Perturbation of the protein landscape after receiving amino acid and protein cargo from EVs changes how the recipient cell might respond to external factors and intrinsic machinations (254,255). The influence of extracellular vesicle cargo on perpetuating legacies of salient environmental experiences is in its infancy (256,257). However, landmark studies have already demonstrated causality in this space.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%